2021
DOI: 10.1002/elps.202100302
|View full text |Cite
|
Sign up to set email alerts
|

Stronger together: Analytical techniques for recombinant adeno associated virus

Abstract: With recent FDA approval of two recombinant adeno‐associated virus (rAAV)‐based gene therapies, these vectors have proven that they are suitable to address monogenic diseases. However, rAAVs are relatively new modalities, and their production and therapy costs significantly exceed those of conventional biologics. Thus, significant efforts are made to improve the processes, methods, and techniques used in manufacturing and quality control (QC). Here, we evaluate transmission electron microscopy (TEM), analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Several studies have reported that AAVs purified using ultracentrifuga- tion techniques contain proteasome contamination. 38 The height value observed by AFM (∼14 nm) was similar to the reported dimension of proteasomes. 39 Core−shell structures with empty inner spaces often cause morphological rupture or distortion in AFM images.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Several studies have reported that AAVs purified using ultracentrifuga- tion techniques contain proteasome contamination. 38 The height value observed by AFM (∼14 nm) was similar to the reported dimension of proteasomes. 39 Core−shell structures with empty inner spaces often cause morphological rupture or distortion in AFM images.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…The population with the smallest height, lower than 14 nm, was considered to be proteasome contamination. Several studies have reported that AAVs purified using ultracentrifugation techniques contain proteasome contamination . The height value observed by AFM (∼14 nm) was similar to the reported dimension of proteasomes …”
Section: Resultssupporting
confidence: 82%
“…■ RESULTS AND DISCUSSION Basic Principles of Interaction between PNA and DNA Oligonucleotides. In our previous report, 33 we used orthogonal analytical techniques including transmission electron microscopy, analytical ultra centrifugation, and CGE to get a better idea of DNA heterogeneity inside rAAV capsids. The complex DNA purity profiles that were observed with CGE naturally caused the question to identify the unknown species.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Although recent reviews have highlighted potential key structural properties of rAAV vectors for use as gene therapy candidates [65][66][67] , no actual data sets with representative rAAV vectors were provided. At the same time, there are numerous recent reports employing individual analytical methods to monitor specific structural attributes of rAAV vectors including chromatography, electrophoresis, light scattering, SV-AUC, TEM, immunoassays and mass spectrometry 48,[68][69][70][71][72][73][74] , yet only a few showing a combination of comparative data sets 72,75,76 . Quality-by-design analysis for rAAV vectors for gene therapy applications have proposed the following CQAs: encapsidated capsids, empty-partially filled capsid ratios, aggregates and deamidated forms 77,78 .…”
Section: Physicochemical Properties and Mechanisms Of Thermal Degrada...mentioning
confidence: 99%